Problems and Solutions for the Flood Control Program in Medan City and its Surroundings - Darman Saragih (Journal of the Civil Engineering Forum, 2023)
Medan City is currently experiencing flooding and this indicates all existing flood control projects implemented over the years have been unsuccessful. Therefore, the main objective of this research is to determine the best solution to overcome floods in the city through a literature study supplemented by a perception survey. The steps implemented include discovering the causes of the flood, determining the failure of the past flood control projects, disclosing the perception of the people affected by floods toward the city government’s commitment, and formulating the best solution to overcome the flood. It was discovered that there are two kinds of floods in Medan city which include the flash/river and the local/residence floods. The flash type was caused by the deforestation in the upstream area of the rivers flowing through the city while the local type is associated with high rainfall, lack of pervious area, and poor urban stormwater management. Moreover, the existing flood mitigation projects were observed to be unsuccessful because they applied the old paradigm with a normalization approach without compensating for the increase in the runoff discharge. This means there is a need to establish naturalization in the upper region of all rivers flowing through the city to reduce river flooding. The maintenance of the existing urban drainage system also needs to be combined with sustainable programs such as storing, absorbing, and reusing strategies to mitigate residence flooding. Furthermore, ten recommendations were proposed to stakeholders to overcome or significantly reduce flooding in Medan City and its surroundings. The first is the alignment of paradigms among stakeholders toward flood management while the last is completing related regulations and law enforcement.